EDA Complexation of Two Donor Molecules Initiating Radical Cation Cyclizations - Kürschner, Julian C. G.; Utikal, Martin; Lezius, Lena; Jeyaseelan, Rubaishan; Næsborg, Line (Synthesis, 2025)
In this study, a catalyst-free EDA complexation of two donor molecules using an acidic solvent is presented. The electron-rich aromatic compound (E)-anethole is slowly protonated by the solvent hexafluoroisopropanol (HFIP), leading to the rapid formation of a photoactive EDA complex between a protonated (E)-anethole and another (E)-anethole molecule. This resulting EDA complex initiates radical chain cyclization reactions under green light irradiation.
Keywords: EDA complex; radical cyclization; catalyst free; photochemistry